Aspectos socioambientais, demográficos e infraestruturais do projeto de assentamento Nova Vida em Upanema/RN - Castro, Paula Monielly Pimenta de (Universidade Federal Rural do Semi-Árido, 2020)
The work results from the study about an agrarian reform settlement, the Nova Vida settlement project, in the rural area of the municipality of Upanema / RN, with the objective of identifying the socio-environmental, demographic and infrastructural aspects. Methodologically, it is an exploratory research with a qualitative approach. For this purpose, bibliographic research was used through several readings of materials such as articles, dissertations, books that provided the basis for the research. Data were collected through the application of fifty-two semi-structured questionnaires with the residents of the settlement, in addition to an interview with a former president of the community association and analysis of the minutes and the pedagogical political project of the local school. The settlement maintains a profile of men and women from other municipalities; settled families made up of father, mother and children came in search of land. In this perspective, the social conditions found in the community regarding the interviewee's family's schooling awaken to a low school level due to incomplete elementary education. The main economic activities of survival developed by the residents is the raising of animals and agriculture. The income obtained by the field worker is low. The view presented by the subjects concerning the environment is worrying; in their concept it has the meaning of plants, having a low understanding of the environmental impacts and the sustainability of natural resources. Therefore, there is concern, but the subjects contradict themselves in practice when they support the work of companies that harm the community by bringing degradation to it. We identified the absence of a proper place for the disposal of garbage and the collection of this is separated for burning; we consider that there is a lack of environmental education to reflect on the impacts on the settlement.
Monografia
Keywords: Aspectos socioambientais. Aspectos Demográficos. Aspectos Infraestruturais. Educação do Campo. Assentamento Nova Vida.; Aspectos demográficos; Aspectos infraestruturais; Educação do campo; Assentamento Nova Vida; Socio-environmental aspects; Demographic aspects; Infrastructure aspects; Rural education; New life settlement; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL